Weight Change Pattern Among Breastfeeding Mothers: One-Year Follow-Up - BORAN, PERRAN; AKTAÇ, ŞULE (My University, 2021)
Objective: Excessive gestational weight gain (GWG) and postpartum weight retention are risk factors for female obesity. The aim of the study was to assess postpartum weight change patterns among 64 Turkish, exclusively breastfed to 6 months and continued to 1 year and beyond, mothers during 1-year follow-up. Materials and Methods: Postpartum women's sociodemographic characteristics and breastfeeding patterns were obtained and anthropometric measurements were determined at five time points (1st, 3rd, 6th, 9th, and 12th months). Results: Mean GWG was 12.2 ± 5.8 kg and mean postpartum weight retention was 4.2 ± 4.9, 4.6 ± 4.8, 3.7 ± 5.4, 2.8 ± 5.0, and 3.3 ± 5.5 kg at 1st, 3rd, 6th, 9th, and 12th months, respectively. According to the results of repeated measure analysis of variance (ANOVA), there was significant time effect in body weight (F = 6.509; p = 0.001), body mass index (BMI) (F = 6.743; p = 0.001), and weight retention (F = 6.509; p = 0.001) measured over 1 year. Bonferroni multiple post hoc tests results showed similar significant changes between 1st-9th months (p < 0.05), 3rd-6th months (p < 0.05), 3rd-9th months (p < 0.05), 3rd-9th months (p < 0.001), and 3rd-12th months (p < 0.05) for body weight, BMI, and weight retention. Two-way repeated measures ANOVA of body weight, BMI, and weight retention by time showed significant interactions for employment status (p < 0.05) and prepregnancy BMI (p < 0.05). Conclusion: These findings highlight the importance of weight management starting from pregnancy to postpartum 1 year.
Keywords: breastfeeding; body mass index; postpartum weight retention; prepregnancy body weight; weight management